Consistent Planning - Pollak, R. A. (Review of Economic Studies, 1968)
Journal Article Consistent Planning Get access R. A. Pollak R. A. Pollak University of Pennsylvania Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 2, April 1968, Pages 201–208, https://doi.org/10.2307/2296548 Published: 01 April 1968